Composite dietary antioxidant index mediates the effect of epilepsy on psychiatric disorders: results from NHANES 2013–2018 - He, Xingyan; Li, Zhiling; Wu, Haotian; Wang, Lifen; Zhang, Yuxin (Frontiers in Neurology, 2024)
BackgroundPsychiatric disorders is a major public health problem and epilepsy contributes significantly to depression. We aimed to explore the relationship between dietary patterns and mental illness in patients with epilepsy.MethodsThe data presented here are based on the 2013–2018 National Health and Nutrition Examination Survey (NHANES). In this study, the t-test and chi-square tests or one-way analysis of variance (ANOVA) were employed for the analysis of continuous and categorical variables, respectively. Restricted cubic splines (RCSs) with four knots were employed to investigate the linear relationship and trend between the Composite Dietary Antioxidant Index (CDAI) and epilepsy and psychiatric disorders, respectively. In instances where the linear relationship was not deemed to be applicable, the CDAI was categorized into four groups based on quartiles. A logistic regression analysis was employed to investigate the relationship between epilepsy and mental disorders under four distinct models. A mediation analysis was employed to ascertain whether CDAI acted as a mediator in the relationship between epilepsy and mental disorders.ResultsPatients with epilepsy had a significantly lower CDAI (p < 0.001) and a significantly higher prevalence of psychiatric disorders (p = 0.02) compared with non-epileptic patients. Mediation modeling showed that CDAI mediated between 3.17 and 5.21% of epilepsy-related psychiatric disorders. In stratified analyses, the prevalence of psychiatric disorders was increased in the second quartile subgroup and the third quartile subgroup of the CDAI dietary index in patients with epilepsy compared with non-epileptic patients.ConclusionOur findings suggest that patients with epilepsy have a high risk of developing psychiatric disorders and that the Composite Dietary Antioxidant Index (CDAI) plays a key role in mediating the relationship between epilepsy and psychiatric disorders.